Archiving Collective Memories and (Dis)owning - Tchokothe, Rémi Armand (Afrika Focus, 2019)
This paper investigates the question of ownership of collective memories in the age of digitized archiving. The United Nations Educational, Scientific and Cultural Organization’s (henceforth Unesco) philosophy of preserving the world cultural heritage has boosted research on African oral literatures. The emphasis on the documentation of endangered cultures of Africa is salutary but also raises some critical questions. The central question this contribution addresses is that of the authorship-ownership of cultural heritage that is being archived in the framework of digital humanities. In essence, the notion of “collective memories” entails that of collective authorship and collective belonging as these memories are passed on from one generation to the other without the claim of singular ownership. A significant example in this line of thought has been the observation by the cultural giant Amadou Hampâté Bâ who ironically pointed out that the real author of The Fortunes of Wangrin (1973), which is attributed to him, is actually the storyteller Wangrin – the cunning interpreter – and members of the whole literary tradition that Wangrin embodied. In the preface of a recently published volume on La question de l’auteur en littératures africaines (Jérôme Roger 2015: 16) the author asks the following pertinent question: how can African literature, both oral and others, invite scholars to rethink the relationship between the anonymity of sources, versions and variants of stories and the constraint for an author’s name imposed by editors? The question has more weight in view of the massive digitization of African oral literatures that mostly takes place in institutions with more economic prestige and which are located outside the African continent. Therefore, the interrogation centres on the role of power with regard to the form in which these (hi)stories are published, where, how and to whom they are accessible, and to the habit of researchers to name people from whom they receive the bulk of knowledge which they transcribe and translate into the academic jargon “informants” instead of giving them more credit by referring to them as research partners or even by recognising them as co-authors. In this vein, the paper rounds up by exploring the possibility of reversing the customary auctorial perspective by bringing into the discussion the idea of “researchers as griots” suggested by (Merolla, Ameka & Dorvlo 2013). KEYWORDS: ARCHIVING AND SILENCING, MEMORICIDE, TEACHERS ON THE FIELD, SELFISH ALTRUISM, RESEARCHERS AS GRIOTS